Clinicopathological correlation of primary and recurrent choroidal neovascularisation following surgical excision in age related macular degeneration. Issue 5 (1st May 1998) - Castellarin, Alessandro A; Nasir, Ma'an A; Sugino, Ilene K; Zarbin, Marco A
Abstract : AIMS/BACKGROUND: Fluorescein angiography and histopathological findings were correlated in two patients with recurrent choroidal neovascular membranes (CNVs) in an attempt to gain insight into the possible causes of recurrent CNVs and into the healing response after CNV excision. METHODS: Two patients with recurrent CNVs underwent repeat excision, and the excised tissue was studied with light and electron microscopy. RESULTS: Incomplete CNV excision probably led to the recurrences. The portion initially excised appears to have been anterior to the RPE in case 1. In both cases, recurrent CNVs contained RPE-like cells suggesting that native RPE can repopulate the dissection bed. The tissue excised at the second operation contained areas with hyperplastic RPE and fragments of Bruch's membrane (external to the RPE basement membrane) in a matrix of fibrillar collagen and fibrocytes, suggesting that initial removal of the CNV can be followed by an abnormal anatomical arrangement of RPE and scarring of Bruch's membrane. CONCLUSIONS: Abnormal resurfacing of the dissection bed by RPE and fibroblasts may underlie, in part, the limited visual outcome often seen after surgical excision of CNVs in age related macular degeneration.